2015
DOI: 10.1021/es505878f
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation as a Natural Antidote to Metallic Nanoparticles Is Overestimated: CuO Sulfidation Yields CuS Nanoparticles with Increased Toxicity in Medaka (Oryzias latipes) Embryos

Abstract: Sulfidation is considered as a natural antidote to toxicity of metallic nanoparticles (NPs). The detoxification contribution from sulfidation, however, may vary depending on sulfidation mechanisms. Here we present the dissolution−precipitation instead of direct solid-stateshell mechanism to illustrate the process of CuO-NPs conversion to CuSNPs in aqueous solutions. Accordingly, the CuS-NPs at environmentally relevant concentrations showed much stronger interference on Japanese medaka (Oryzias latipes) embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…48,49 The current knowledge on mechanistic fate/transformation reactions of ENMs in the environment does not allow modelers to predict the likelihood of how (many) particles of a given ENM have been transformed. 50 Many ENMs (e.g. However, recent toxicology data suggests it may be necessary to specifically model the further fate of the silver sulfides formed.…”
Section: Transformation Reactionsmentioning
confidence: 99%
“…48,49 The current knowledge on mechanistic fate/transformation reactions of ENMs in the environment does not allow modelers to predict the likelihood of how (many) particles of a given ENM have been transformed. 50 Many ENMs (e.g. However, recent toxicology data suggests it may be necessary to specifically model the further fate of the silver sulfides formed.…”
Section: Transformation Reactionsmentioning
confidence: 99%
“…In other animal model toxicology studies of intravenously injected silica nanoparticles, hepatocyte necrosis and mononuclear inflammation at the portal area were observed [45], indicating the possibility of liver toxicity due to silica nanoparticles. Metal-based photothermal nanoagents, such as CuS, had some limitations associated with toxicity [31,46]. Feng et al [31] have suggested that CuS-based nanoparticles can serve as promising photothermal agents; however, their biodistribution study showed that intravenously administrated CuS nanomaterials were mainly present in the spleen, liver, and lung, organs that are responsible for eliminating pathogens via the reticuloendothelial system (RES).…”
mentioning
confidence: 99%
“…One can follow the procedures used by many researchers: addition of NPs to the solution, brief sonication as needed, mixing on an orbital shaker for the duration of the test to minimize mass transfer resistance, and periodic measurements using centrifugal filtration with a 3 or 10 kDa filter to separate ions from NPs (Liu et al, 2010;Ma et al, 2012). Testing may eventually lead to the need for a larger MWCO filter that includes metal-macromolecule complexes in the "filterable/ bioavailable fraction" to be measured in the test (Ma et al, 2014;Li et al, 2015). These are simple batch tests adaptable to any type of solution that best represents the system of interest (e.g.…”
Section: Samples Of System Typesmentioning
confidence: 99%